Modeling of heavy reflectors using DONJON-5. (May 2019) - Taforeau, Julien; Muller, Marc; Salino, Vivian
Highlights: The Koebke method is simple and easy to implement. The Koebke method is relevant for heavy reflector modeling. The Koebke method is not sensitive to control rod insertion. The Koebke method is not sensitive to the average burnup core. Abstract: The IRSN code sequence based on DRAGON-5/DONJON-5 codes has been developed as part of the ORION project. Its goal is to provide a code sequence and computation scheme that works effectively for the study of PWR in operating conditions. The first part of the paper presents the differences between light and heavy reflectors and prove the need to validate the current computation scheme for heavy reflectors. The second part presents the validation of the DRAGON-5/DONJON-5 computation scheme by comparison of the relative power distribution with CASMO-5 which is considered as the deterministic reference for the present study. The last part deals with the optimization of the computation scheme to improve the heavy reflector model.